Functional and Therapeutic Significance of Tumor-Associated Macrophages in Colorectal Cancer - Li, Yitong; Chen, Zhenmei; Han, Jiahao; Ma, Xiaochen; Zheng, Xin; Chen, Jinhong (Frontiers in Oncology, 2022)
The role of the tumor microenvironment (TME) in the progression of colorectal cancer (CRC) and its acquisition of resistance to treatment becomes the research hotspots. As an important component of TME, the tumor-associated macrophages (TAMs) regulate multiple critical oncogenic processes, including occurrence, proliferation, metastasis, and drug resistance in CRC. In this review, we have discussed the functional and therapeutic significance of TAMs in CRC. M1 macrophages act as the tumor suppressor while M2 macrophages promote CRC. The polarization of TAMs is mainly regulated by the pathways such as NF-κB pathways, STAT3 pathways, Wnt5a pathways, and PI3K pathways in CRC. Furthermore, the M2 polarization of TAMs is not only controllable but also reversible. Finally, we provide insights into the TAMs-targeted therapeutic strategies.